Does the Addition of a Vascularized Fibula Improve the Results of a Massive Bone Allograft Alone for Intercalary Femur Reconstruction of Malignant Bone Tumors in Children?. Issue 6 (June 2021) - Errani, Costantino; Alfaro, Patricio A.; Ponz, Virginia; Colangeli, Marco; Donati, Davide Maria; Manfrini, Marco
Abstract: Background: Massive bone allograft with or without a vascularized fibula is a potentially useful approach for femoral intercalary reconstruction after resection of bone sarcomas in children. However, inadequate data exist regarding whether it is preferable to use a massive bone allograft alone or a massive bone allograft combined with a vascularized free fibula for intercalary reconstructions of the femur after intercalary femur resections in children. Because the addition of a vascularized fibula adds to the time and complexity of the procedure, understanding more about whether it reduces complications and improves the function of patients who undergo these resections and reconstructions would be valuable for patients and treating physicians. Questions/purposes: In an analysis of children with bone sarcomas of the femur who underwent an intercalary resection and reconstruction with massive bone allograft with or without a vascularized free fibula, we asked: (1) What was the difference in the surgical time of these two different surgical techniques? (2) What are the complications and number of reoperations associated with each procedure? (3) What were the Musculoskeletal Tumor Society scores after these reconstructions? (4) What was the survival rate of these two different reconstructions? Methods: Between 1994 and 2016, we treated 285 patients younger than 16 years with a diagnosis of osteosarcoma or Ewing sarcoma of the femur. In all, 179 underwent resection and reconstruction of the distal femur and 36 patients underwent resection and reconstruction of the proximal femur. Additionally, in 70 patients with diaphyseal tumors, we performed total femur reconstruction in four patients, amputation in five, and a rotationplasty in one. The remaining 60 patients with diaphyseal tumors underwent intercalary resection and reconstruction with massive bone allograft with or without vascularized free fibula. The decision to use a massive bone allograft with or without a vascularized free fibula was probably influenced by tumor size, with the indication to use the vascularized free fibula in longer reconstructions. Twenty-seven patients underwent a femur reconstruction with massive bone allograft and vascularized free fibula, and 33 patients received massive bone allograft alone. In the group with massive bone allograft and vascularized fibula, two patients were excluded because they did not have the minimum data for the analysis. In the group with massive bone allograft alone, 12 patients were excluded: one patient was lost to follow-up before 2 years, five patients died before 2 years of follow-up, and six patients did not have the minimum data for the analysis. We analyzed the remaining 46 children with sarcoma of the femur treated with intercalary resection and biological reconstruction. Twenty-five patients underwent femur reconstruction with a massive bone allograft and vascularized free fibula, and 21 patients had reconstruction with a massive bone allograft alone. In the group of children treated with massive bone allograft and vascularized free fibula, there were 17 boys and eight girls, with a mean ± SD age of 11 ± 3 years. The diagnosis was osteosarcoma in 14 patients and Ewing sarcoma in 11. The mean length of resection was 18 ± 5 cm. The mean follow-up was 117 ± 61 months. In the group of children treated with massive bone allograft alone, there were 13 boys and eight girls, with a mean ± SD age of 12 ± 2 years. The diagnosis was osteosarcoma in 17 patients and Ewing sarcoma in four. The mean length of resection was 15 ± 4 cm. The mean follow-up was 130 ± 56 months. Some patients finished clinical and radiological checks as the follow-up exceeded 10 years. In the group with massive bone allograft and vascularized free fibula, four patients had a follow-up of 10, 12, 13, and 18 years, respectively, while in the group with massive bone allograft alone, five patients had a follow-up of 10 years, one patient had a follow-up of 11 years, and another had 13 years of follow-up. In general, there were no important differences between the groups in terms of age (mean difference 0.88 [95% CI -0.6 to 2.3]; p = 0.26), gender (p = 0.66), diagnosis (p = 0.11), and follow up (mean difference 12.9 [95% CI-22.7 to 48.62]; p = 0.46). There was a difference between groups regarding the length of the resection, which was greater in patients treated with a massive bone allograft and vascularized free fibula (18 ± 5 cm) than in those treated with a massive bone allograft alone (15 ± 4 cm) (mean difference -3.09 [95% CI -5.7 to -0.4]; p = 0.02). Complications related to the procedure like infection, neurovascular compromise, and graft-related complication, such as fracture and nonunion of massive bone allograft or vascularized free fibula and implant breakage, were analyzed by chart review of these patients by an orthopaedic surgeon with experience in musculoskeletal oncology. Survival of the reconstructions that had no graft or implant replacement was the endpoint. The Kaplan-Meier test was performed for a survival analysis of the reconstruction. A p value less than 0.05 was considered significant. Results: The surgery was longer in patients treated with a massive bone allograft and vascularized free fibula than in patients treated with a massive bone allograft alone (10 ± 0.09 and 4 ± 0.77 hours, respectively; mean difference -6.8 [95% CI -7.1 to -6.4]; p = 0.001) . Twelve of 25 patients treated with massive bone allograft and vascularized free fibula had one or more complication: allograft fracture (seven), nonunion (four), and infection (four). Twelve of 21 patients treated with massive bone allograft alone had the following complications: allograft fracture (five), nonunion (six), and infection (one). The mean functional results were 26 ± 4 in patients with a massive bone allograft and vascularized free fibula and 27 ± 2 in patients with a massive bone allograft alone (mean difference 0.75 [95% CI -10.6 to 2.57]; p = 0.39). With the numbers we had, we could not detect a difference in survival of the reconstruction between patients with a massive bone allograft and free vascularized fibula and those with a massive bone allograft alone (84% [95% CI 75% to 93%] and 87% [95% CI 80% to 94%], respectively; p = 0.89). Conclusion: We found no difference in the survival of reconstructions between patients treated with a massive bone allograft and vascularized free fibula and patients who underwent reconstruction with a massive bone allograft alone. Based on this experience, our belief is that we should reconstruct these femoral intercalary defects with an allograft alone and use a vascularized fibula to salvage the allograft only if a fracture or nonunion occurs. This approach would have resulted in about half of the patients we treated not undergoing the more invasive, difficult, and risky vascularized procedure. Level of Evidence Level III, therapeutic study.